Quality control material for plasma fibrinogen test produced from purified human fibrinogen. Issue 4 (2003) - Okuda, Masahiro; Uemura, Yahiro; Tatsumi, Noriyuki
Abstract : Plasma fibrinogen measurement is a routine laboratory procedure commonly performed on automated coagulation analysers. Its determination is quantitative, not quantitative. Yet, a lack of precision has been an issue for fibrinogen measurement. A control material derived from plasma comprises many proteins, inhibitors and fatty acids, any or all of which can interfere in the fibrinogen assay. This study has attempted to develop a quality control material using purified human fibrinogen and has compared measurement precision between both purified and plasma materials. Purified fibrinogen was prepared using Cohn fraction 1 and glycine precipitation. Purified fibrinogen clottability was greater than 95%, with no main plasma proteins, lipids or fibrinogen degradation products observed. Two purified control materials were lyophilized at normal (2.30 g l m1 ) and abnormal (1.20 g l m1 ) levels of fibrinogen concentration. Precision was evaluated using a liquid-type reagent, Thrombocheck Fib(L), on automated coagulation analysers. Coefficient of variation for within-run, intraday and between-day precision of the purified materials was 0.7-3.5%. In comparison, the coefficient of variation for plasma materials ranged from 1.2 to 5.3%. These results suggest that materials prepared from purified fibrinogen can be useful to laboratory quality control by improving overall precision of fibrinogen measurement and are applicable to automated coagulation analysers.